(untitled) (مجلة إحالات, 2026)
This article is part of a reflexion on the teaching and learning French particularly in its component of writing at secondary school in Morocco. This language, whose status varies, in educational terms, between the language taught and the language of instruction, does pose problems and challenges in the teaching process. Our target audience in this study is common core students. The corpus is based on writing productions which we have studies and analysed so to highlight the mistakes, in terms of gender, that are frequently made by students; these mistakes are attributed to the interference of their native language or language of communication while learning a foreign language.